Venus Williams - Aronson, Virginia; Andrews, Elaine K. (Philadelphia : Chelsea House Publishers, 1999)
A biography of the teenage tennis player who was ranked among the top ten women players in the world in 1998.
Includes bibliographical references (p. 63) and index.
Keywords: Williams, Venus, -- 1980- -- Juvenile literature; Williams, Venus, -- 1980-; Tennis players -- United States -- Biography -- Juvenile literature; African American women tennis players -- Biography -- Juvenile literature; Tennis players; Women -- Biography; African Americans -- Biography